PCG-Generated Randomness: A NIST Analysis of 100-Million Bits - Metin, Zülfiye Beyza; Özkaynak, Fatih (My University, 2025)
The generation of random numbers is crucial for various applications, including cryptography, simulation, sampling, and statistical analysis. Cryptography utilizes random numbers to secure communication through the generation of encryption keys, thereby safeguarding sensitive information from unauthorized access. This study aims to evaluate the randomness and suitability of the Permuted Congruential Generator (PCG) algorithm for cryptography applications, through testing its generated random numbers using the National Institute of Standards and Technology (NIST) statistical tests. A novel method is proposed for generating 100 million bits using the PCG algorithm. The generated random numbers are then subjected to NIST testing. The results indicate that the PCG-generated random numbers pass most relevant statistical tests and comply with the standards of randomness necessary for cryptography. In conclusion, the PCG algorithm is demonstrated to be a robust, dependable, and appropriate random number generator for cryptography and other applications requiring random numbers.
Keywords: Security; Randomness; PCG; NIST